2003
DOI: 10.2169/internalmedicine.42.897
|View full text |Cite
|
Sign up to set email alerts
|

Pulseless Hematochezia: Takayasu's Arteritis Associated with Ulcerative Colitis

Abstract: A 36-year-old womanwith ulcerative colitis presented with fever, chest and back pain, and fatigue sensation of the arm. Her upper limb pulses were absent. Angiography showed multiple aneurysms of the aorta and its branches, consistent with Takayasu's arteritis. She showed HLA-B35but no B52, which is the typical haplotype among the coexistence cases of both diseases. Prednisolone was effective. The possible pathogenic association of the disorders is discussed. (Internal Medicine 42: 897-898, 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Several vascular complications have been described associated with UC including different forms of aortitis [16], vasculitis [17], capillaritis [18] and panniculitis with vasculitis [19]. There are several reports showing a combination of Takayasu's arteritis and UC [20,21]. Activation of coagulation system could develop in some patients with aortic [22][23][24][25], retinal artery [26], splanchnic artery, portal vein [27] and pulmonary artery [28] embolism, and disseminated intravascular coagulopathy (DIC) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several vascular complications have been described associated with UC including different forms of aortitis [16], vasculitis [17], capillaritis [18] and panniculitis with vasculitis [19]. There are several reports showing a combination of Takayasu's arteritis and UC [20,21]. Activation of coagulation system could develop in some patients with aortic [22][23][24][25], retinal artery [26], splanchnic artery, portal vein [27] and pulmonary artery [28] embolism, and disseminated intravascular coagulopathy (DIC) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Like TA and UC, SAT has been thought to be associated with certain types of HLA, especially B35 (4). Hokama et al reported a case of TA associated with UC, which was positive for HLA-B35, not B52 (11). In addition, Ohsako et al reported, following the analysis of 56 six Japanese patients with SAT, that SAT is associated with HLA-B35 and B67 (5).…”
Section: Discussionmentioning
confidence: 99%
“…Hokama et al(2003) reported a case with coexistence of UC and TA, in which the patient carried co B5 and B52, although a direct genetic link was not identified.…”
Section: Discussionmentioning
confidence: 99%